The Relationship between Syntax and Semantics in the case of Ma`ani Nahwi in Arabic Grammar and the idea of Modistae in Latin - Yaacob, Solehah@Nik Najah Fadilah (2009)

(untitled)
The research emphasizes on the connection between the Arabic concept of ma`ani nahwi and modistae in Latin. In order to identify this connection, the researcher has to elaborate on the role of Aristotle`s categories in influencing the concept of modistae in the Middle Ages then the paper will reevaluate of Muslim philosophers such as al-Farabi, Avicenna and Averoes. Then clarify the role of Jurjani in introducing his concept of Nazm. As a result of these also will enhance the understanding of the relationship between syntax and semantic.